PENGARUH JARAK ANTARA ELEKTRODA PADA REAKTOR ELEKTROKOAGULASI TERHADAP PENGOLAHAN EFFLUENT LIMBAH CAIR PABRIK KELAPA SAWIT - Edy Saputra, Farida Hanum (Jurnal Teknik Kimia USU, 2016)
Liquid waste from palm oil mill continues to grow concurrently with the increased production of palm oil in Indonesia. Technical processing of palm oil mill effluent using anaerobic ponds are less efficient because it requires large area besides palm oil mill effluent produce greenhouse gases caused by carbon dioxide gases that are generated. Therefore we need another alternative technology such as electrocoagulation as advanced technology in processing wastewater effluent from an anaerobic column. Electrocoagulation is a wastewater treatment system that is capable of eliminating pollutants and produce hydrogen gas simultaneously as revenue to offset operating costs. This study aims to determine the effect and the best inter electrode distance to reduce pollutant parameters such as chemical oxygen demand, total solids and total suspended solids. The type of electrode material used is aluminum, the reactor dimensions 12 cm x 12 cm x 36 cm with 3 hours of operating time, voltage 10 volts, variations of inter electrode distance 0.5 cm; 1.0 cm; 1.5 cm and 2.0 cm. Samples were taken from palm oil mill PT. PP London Sumatra in Bagerpang, Tanjung Morawa. The results obtained by the percentage reduction in COD, TSS TS and the highest was 72.897% at 1.0 cm; 67.292% at 1.5 cm and 96.429% at 1.5 cm. Best distance between the electrodes was 1.5 cm.